Education for the Anthropocene: Planetary health, sustainable health care, and the health workforce. (2nd October 2020) - Barna, Stefi; Maric, Filip; Simons, Julia; Kumar, Shashank; Blankestijn, Peter J.
Abstract: Over the past few centuries, human activity has wrought dramatic changes in the natural systems that support human life. Planetary health is a useful concept for health profession education (HPE) teaching and practice because it situates health within a broader understanding of the interdependent socio-ecological drivers of human and planetary health. It facilitates novel ways of protecting both population health and the natural environment on which human health and well-being depends. This paper focuses on the climate crisis as an example of the relationship between environmental change, healthcare, and education. We analyze how HPE can help decarbonize the healthcare sector to address both climate change and inequity in health outcomes. Based on the healthcare practitioner's mandate of beneficence, we propose simple learning objectives to equip HPE graduates with the knowledge, skills, and values to create a sustainable health system, using carbon emission reductions as an example. These learning objectives can be integrated into HPE without adding unduly to the curriculum load.